Estratégias farmacológicas para potencialização do efeito vasodilatador induzido pela fotobiomodulação - Moraes, Luis Henrique Oliveira de (2021)
Previous work indicates that the red LASER (660 nm) induces vascular relaxation by a mechanism Nitric Oxide (NO) dependent. NO activates soluble guanylate cyclase (sGC), which produce cGMP, the main effector in the vasodilation pathway. An interesting pharmacological strategy is to control the levels of intracellular cGMP, preventing its efflux (with Multidrug Resistant Proteins blockers, such as MK-571 and probenecid), or preventing its degradation (such as Sildenafil, which inhibits the enzyme responsible for cGMP degradation, the phosphodiesterase-5 PDE5). The aim was to study pharmacological strategies to improve vasodilation LASER effect in normotensive and L-NAME hypertensive rats. It was performed vascular reactivity study in isolated aortic rings from normotensive and hypertensive rats, with a single LASER application and Sodium Nitroprusside (SNP) treatment. In aortic rings from normotensive rats, MK-571, probenecid and Sildenafil potentiated the relaxation induced by LASER, compared to control. The vasodilation induced by SNP was potentiated by MK-571 and Sildenafil, compared to control. In aortic rings from hypertensive rats, vasodilation effect induced by LASER and by SNP was potentiated just by MK-571, compared to control, with no potentiation by Sildenafil. The results support the evidence that the vasodilation induced by red LASER is potentiated by MK-571 and sildenafil in aortic rings from normotensive rats. However, in aortic rings from L-NAME hypertensive rats the potentiation in vasodilation was induced just by MK-571.